Micronutrient Intake and Preeclampsia: The Protective Role of Vitamins C and D - Siska Indrayani; Rina Oktaviana (Lembaga Publikasi Ilmiah Nusantara, 2026)
Preeclampsia is a major hypertensive disorder of pregnancy that contributes significantly to maternal and perinatal morbidity. This study aimed to examine the association between maternal micronutrient intake, particularly vitamin C and vitamin D, and the occurrence of preeclampsia among pregnant women. A case–control study was conducted in Padang, West Sumatra, involving 66 pregnant women in the third trimester: 33 with preeclampsia and 33 without. Micronutrient intake was assessed using a Semi-Quantitative Food Frequency Questionnaire. Data were analyzed using the Mann–Whitney test and logistic regression analysis. The results showed significant differences in vitamin C and vitamin D intake between the two groups. Multivariate analysis indicated that vitamin D intake and maternal education level were significantly associated with preeclampsia, whereas vitamin C intake was not significantly associated after adjustment for confounding variables. These findings suggest that adequate vitamin D intake during pregnancy may help reduce the risk of preeclampsia. Nutritional interventions during antenatal care may help improve maternal health outcomes.